The well-being of Indonesian university students during the pandemic: Smartphone use and sleep quality - Bianca Marella; Grace Eugenia Sameve (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
Online learning and the lack of social interactions during lockdown pushed numerous college students to live employing the internet and social media. This study investigates students' well-being and its associated factors in relation to smartphone use and sleep quality among Indonesian university students during the pandemic. A sample of 327 undergraduate students (68 males and 259 females) anonymously completed the Smartphone Addiction Scale – Short Version (SAS-SV), WHO-Five Wellbeing Index (WHO-5), and Pittsburgh Sleep Quality Index (PSQI), along with several socio-demographic data via an online survey. The data was then analyzed with hierarchical linear regression. The results indicate that gender, perceived physical health, smartphone use, and sleep quality were associated with well-being in university students. The final model predicted 23.4 percent of the WHO-5 scores with a significant increase in predictive value by adding perceived physical health and sleep quality. Therefore to enhance well-being among Indonesian university students, suitable physical activities, good sleeping habits, and controlled smartphone use is needed.